أثر البيئة في تعلم اللغة - Ana Achoita (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2017)
Language is a means of communicating a person with others. In language learning, especially arabic the environment has a great influence where language skills for the first time through hearing. Environment is one of the influential external factors in language development. Because the environment is a condition where one can practice language activity, for example conversation, speech, race, and language game.